Pengaruh Motivasi, Self Efficacy, dan Komitmen Karyawan terhadap Kinerja Perawat di Rumah Sakit Hermina Depok - Nurianna Harianja; Rokiah Kusumapraja; CSP Wekadigunawan (Jurnal Health Sains, 2022)
Employee performance is one of the factors that play an important role in achieving company goals and individual goals. Performance is an ability that a person has to complete a task given by superiors so that it is completed with one's abilities, willpower and skills. The high low performance of an employee is determined by factors that affect him directly or indirectly. This research aims to test the influence of motivation, self-efficacy, and employee commitment to the performance of nurses at Hermina Depok Hospital. The data used is the result of the spread of questionnaires directly from September to November 2020 at Hermina Depok Hospital.The sampling technique uses proportional systematic sampling where there are 200 samples from two different staffing statuses, namely permanent employees and contracts. There are four variables in this study, namely motivation, self-efficacy, and employee commitment and performance. The research instrument uses a questionnaire and is measured using the likert scale. The data is analyzed using the Structural Equation Model (SEM). The results showed that employee motivation, self-efficacy, and commitment had a positive and significant effect on the performance of nurses, both partially and simultaneously